І. LECHNER: CONCEPTUALIZATION OF THE CONCEPT OF MORAL IN THE HUNGARIAN LANGUAGE - LECHNER, І. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. In the public consciousness, morality is a religious, legal, philosophical, social category. One of its most common definitions is that morality is a set of norms judged to be correct by a society, varying from age to age and community to community. In the study, however, we place our previous knowledge of morality in a novel light. Originality. We examine the concept of ‘morality’ from the perspective of cognitive language theory. The topicality of the research is given by the fact that the metaphor research on the named concept has not been performed in the Hungarian language so far. Purpose. The aim of the research is to construct a lay model in the Hungarian language based on the conceptual metaphor morality is strength through the systematic analysis of metaphorical linguistic expressions, thus presenting a slice of the metaphorical conceptualization of the concept of moral. Methods. The focus of the study is the analysis of the collected material, for which we used the methodology of corpus linguistics, so we followed the “bottom-up” direction of analysis. Empirical research is divided into two major parts. First, we compiled the language corpus from a Hungarian database. For this, we used the search term erkölcs (‘moral’) with whole sentence concordance. For the Hungarian language, we used the database of a newer, expanded version of the Hungarian National Text Library. The corpus contains 3000 randomly selected linguistic terms, of which 2216 are considered metaphorical. Results. As result of corpus-based research and metaphor analysis, we identified and systematized conceptual metaphors. In the present study, we present some of the research, namely the qualitative and quantitative analysis of the structural metaphors of the metaphor morality is strength. In doing so, we point to the metaphorical nature of language and thinking, as well as the fundamental role of cognitive linguistics in philosophical and ethical thinking. Conclusion. The analysis revealed that – makes a significant contribution to the conceptualization of the concept of moral. Numerous linguistic examples prove that Hungarian speakers, during the process of interpretation, project certain properties of force as a physical phenomenon into the struggle in the figurative sense, while trying to remain moral. The research confirmed that the concept of moral built by Lakoff (1996) and Lakoff – Johnson (1999) on the basis of intuitive linguistic examples is indeed manifested in live speech in Hungarian.